KANDUNGAN LOGAM BERAT Pb PADA AIR BERSIH DAN PADA DARAH WANITA USIA SUBUR DI KOTA SEMARANG - Wikri Eko Putra; Onny Setiani; Nurjazuli Nurjazuli (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
The Determination of water quality status needs to be done as a references for monitoring water contamination, one of which is by heavy lead metals. Bandarharjo is one of the coastal areas in Semarang that has an industry around it that produces liquid waste that contain lead metal, so it has the potential to polluted clean water sources in the region. This study aims to determine lead pollution in dug well water and deep ground water also blood lead level of women of childbearing age at Bandarharjo Health Center, North Semarang District. The population in this observational analytic study were all women of childbearing age in the working area of the Bandarharjo Public Health Center, which numbered 50 people. Samples were taken by purposive sampling technique, women of childbearing age between 15 and 49 years with a total of 31 respondents. Examination of blood lead levels is carried out using the AAS (Atomic Absorption Spectrophotometry) method. Data analysis was performed using the Chi Square test with a value of 5%. The average blood lead level is 78.08 μg / dL with a range of 54.2 - 99.7 μg / dL. The content of lead heavy metals in clean water has an average value of 0.295 mg / L with a range of 0.080 - 0.446 mg / L. There is a relationship between the quality of clean water sources with blood lead level of women of childbearing age with a p-value of 0.041 (<0.05) with a Ratio of 3.020 (95% CI = 1.043 - 8.739). From this study can be concluded that lead was found in clean water and blood of women of childbearing age (WUS) in the working area of Bandarharjo North Semarang Health Center.